The Influence of Environmental Policy on Innovative Behaviour: An Econometric Study - Jens Hemmelskamp (Fondazione Eni Enrico Mattei (FEEM), 1999)
The paper examines the determinants that influence the environmental innovation behaviour of companies in Germany in a multivariate context by using data from the Mannheimer Innovations Panel 1993, which was part of the Community Innovation Survey. The objective is to analyse the general structures of the determinants of environmental innovation, as well as the specific impact of environmental policy instruments as an integral part of this framework. The pressure of environmental policy instruments on the innovation behaviour of companies is reproduced by indicators, which are investigated in a written survey at the level of the German Chambers of Commerce.
Keywords: Q58; O31; L21; 330; Determinants of innovation; Environmental innovation; Environmental policy; Environmental standards; Environmental taxes; Firms; Innovation; Umweltschutz; Umweltmanagement; Umweltpolitik; Theorie; Deutschland